2014
DOI: 10.1364/oe.22.024507
|View full text |Cite
|
Sign up to set email alerts
|

Energy weighted x-ray dark-field imaging

Abstract: Abstract:The dark-field image obtained in grating-based x-ray phasecontrast imaging can provide information about the objects' microstructures on a scale smaller than the pixel size even with low geometric magnification.In this publication we demonstrate that the dark-field image quality can be enhanced with an energy-resolving pixel detector. Energy-resolved x-ray dark-field images were acquired with a 16-energy-channel photon-counting pixel detector with a 1 mm thick CdTe sensor in a Talbot-Lau x-ray interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Spectral detectors have been used for phase-contrast measurements to increase image contrast for both radiography and computed tomography interrogation. [7][8][9][10] Others have determined that there is a particle-size selectivity in gratings-based dark field measurements, and experimental data acquired at a synchrotron photon source have validated this theory. 11 This particle-size selectivity is an additional signature that can help to determine physical characteristics of a sample and may help discriminate between materials that could not otherwise be differentiated with other measurement methods.…”
Section: Introductionmentioning
confidence: 94%
“…Spectral detectors have been used for phase-contrast measurements to increase image contrast for both radiography and computed tomography interrogation. [7][8][9][10] Others have determined that there is a particle-size selectivity in gratings-based dark field measurements, and experimental data acquired at a synchrotron photon source have validated this theory. 11 This particle-size selectivity is an additional signature that can help to determine physical characteristics of a sample and may help discriminate between materials that could not otherwise be differentiated with other measurement methods.…”
Section: Introductionmentioning
confidence: 94%
“…They are able to access information not only about the attenuation properties of the observed object, but also of phase and scattering properties. Thus, information about the sample’s microstructure and refractive properties, related to ultra-small-angle X-ray scattering, can be accessed 5 , 6 . Furthermore, previous studies have demonstrated a relation between the scattering signal and the size of structural features for the prior mentioned imaging modalities 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…While some papers [15][16][17] have recently reported the demonstration of the combination of the multi-wavelength method and the Talbot-Lau interferometer mainly for visibility-contrast imaging, we focus on the phase imaging in this paper and take thorough advantage of the multi-wavelength with TOF technique at a pulsed neutron source. We report the demonstration of Talbot-Lau interferometry with TOF method and the wavelength-resolved analysis for highly precise and accurate differential-phasecontrast imaging.…”
mentioning
confidence: 99%